Electrical analysis of fresh, excised human skin: a comparison with frozen skin - Kasting, G B; Bowman, L A (Pharmaceutical research, 1990)
Samples of human allograft skin prepared without freezing ("fresh skin") were found to have electrical and sodium ion transport properties which differed only slightly from those of skin which had been similarly treated but stored frozen ("frozen skin"). The fresh skin samples were less permeable to sodium ions during passive diffusion and less conductive than frozen skin at low current levels. They were more permselective for sodium versus chloride during constant-current iontophoresis and showed slightly more asymmetry in their current-voltage properties. Overall, the electrical behavior of the two tissues was similar enough to support the use of frozen tissue in iontophoresis studies. However, caution should be exercised when considering the use of frozen skin for applications, such as those based on electroosmosis, where the observed differences could have a major impact on the results.